2015
DOI: 10.2214/ajr.14.13357
|View full text |Cite
|
Sign up to set email alerts
|

JOURNAL CLUB: Molecular Breast Imaging at Reduced Radiation Dose for Supplemental Screening in Mammographically Dense Breasts

Abstract: OBJECTIVE The purpose of this study was to assess the diagnostic performance of supplemental screening molecular breast imaging (MBI) in women with mammographically dense breasts after system modifications to permit radiation dose reduction. SUBJECTS AND METHODS A total of 1651 asymptomatic women with mammographically dense breasts on prior mammography underwent screening mammography and adjunct MBI performed with 300-MBq 99mTc-sestamibi and a direct-conversion (cadmium zinc telluride) gamma camera, both int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 33 publications
(54 reference statements)
1
95
0
Order By: Relevance
“…Furthermore, there are an expanding number of states with legislation on breast density driven by patient advocacy group concern regarding the limited sensitivity of mammography in women with dense breasts. The work reported by Brem et al in this issue, as well as other recently published studies, are important to ensure that clinical use of supplemental screening approaches continue to be evidence-based (4,20). Determination of the best supplemental screening tool will likely require direct comparison of the cancer detection rate, recall rate, and number of false-positive examinations in large, prospective multiinstitutional trials and include additional considerations such as radiation dose, cost, and accessibility.…”
Section: See Page 678mentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, there are an expanding number of states with legislation on breast density driven by patient advocacy group concern regarding the limited sensitivity of mammography in women with dense breasts. The work reported by Brem et al in this issue, as well as other recently published studies, are important to ensure that clinical use of supplemental screening approaches continue to be evidence-based (4,20). Determination of the best supplemental screening tool will likely require direct comparison of the cancer detection rate, recall rate, and number of false-positive examinations in large, prospective multiinstitutional trials and include additional considerations such as radiation dose, cost, and accessibility.…”
Section: See Page 678mentioning
confidence: 98%
“…The reduction in administered activity did not adversely affect image quality and did not have a statistically significant effect on the cancer detection rate. The resulting whole-body effective dose equivalent of the standard-dose examinations ranges from 5.9 to 9.4 mSv, which decreases to approximately 2.4 mSv for the low-dose examinations (19,20). For comparison, the effective dose equivalent of digital mammography is approximately 0.44 mSv and 1.2 mSv for digital mammography combined with tomosynthesis (19).…”
Section: See Page 678mentioning
confidence: 99%
See 1 more Smart Citation
“…More extensively, a Mayo Clinic group has explored using 99m Tc-sestamibi and dual-head cameras for supplemental screening in women with dense breasts (45,46). As shown in Table 1, the sensitivity and specificity of MBI compare quite favorably with other methods of supplemental screening.…”
Section: Screeningmentioning
confidence: 99%
“…Studies have shown an improvement in breast cancer detection in dense breast, with cancer detection rate per 1000 women increasing from 3.2 for mammography alone to 12.0% with supplemental MBI. 153 A review of the literature shows sensitivity ranging from 91% -96%, with specificity of 60% -77% for MBI alone, 154 and meta-analysis of published literature reported 95% sensitivity and 80% specificity. 155 A major limitation of MBI is its high radiation dose which has the potential to cause mutation to the rapidly dividing cells in dense breasts.…”
Section: Imaging the Dense Breastmentioning
confidence: 99%